Dihydroartemisinin promoted FXR expression independent of YAP1 in hepatocellular carcinoma. Issue 6 (26th May 2022) - Guo, Yinglin; Peng, Qing; Hao, Liyuan; Ji, Jingmin; Zhang, Zhiqin; Xue, Yu; Liu, Yiwei; Gao, Yuting; Li, Caige; Shi, Xinli
Abstract: Loss of FXR, one of bile acid receptors, enlarged livers. Yes‐associated protein 1 (YAP1), a dominant oncogene, promotes hepatocellular carcinoma (HCC). However, the relationship between FXR and YAP1 was unspecified in bile acid homeostasis in HCC. Here, we used TIMER2.0, the Cancer Genome Atlas (TCGA) Database, and Kaplan–Meier Plotter Database and discovered that FXR was positively correlated with better prognosis in liver cancer patients. Our previous research showed that dihydroartemisinin (DHA) inhibited cell proliferation in HepG2 and HepG22215 cells. However, the relationship of YAP1 and the bile acid receptor FXR remains elusive during DHA treatment. Furthermore, we showed that DHA improved FXR and reduced YAP1 in the liver cancer cells and mice. Additionally, the expression of nucleus protein FXR was enhanced in Yap1 LKO mice with liver cancer. DHA promoted the expression level of whole and nuclear protein FXR independent of YAP1 in Yap1 LKO mice with liver cancer. DHA declined cholesterol 7α‐hydroxylase, but not sterol 27‐hydroxylase, and depressed cholic acid and chenodeoxycholic acid of liver tissue in Yap1 LKO mice with liver cancer. Generally, our results suggested that DHA improved FXR and declined YAP1 to suppress bile acid metabolism. Thus, we suggested that FXR acted as a potential therapeutic target in HCC.